The Administration of Wine in Ugarit - Matoïan, Valérie (Die Welt des Orients, 2018)
The present contribution will focus on the information provided by the texts from Ugarit concerning the specific matter of the management of wine by the central administration of the kingdom, specially registers of vineyards, deliveries of wine to the administration, supplies of wine from the administration, and the storage of wine. It also comments on terms referring to vine, vineyards, (vine-)stock, grapes, raisin, and measures of capacity. This information will be supplemented by archaeological and iconographical data, also considering the physical geography of the kingdom.